Behavioral physical activity counselling to promote an active healthy lifestyle among adolescent psychiatric outpatients. The TRANSPAC-study - Christin Lang; Anne Bik; Alexandre N. Datta; Mark Brotzmann; Leila Tarokh; Markus Gerber (Bern Open Publishing, 2024)
Introduction Mental health disorders are one of the main reasons for disability in adolescents worldwide (Dahl et al., 2018). Sleep disturbances are an important contributor to a vicious cycle of increased vulnerability during this developmental period. Interventions that improve sleep are suggested to improve psychosocial outcomes. One such intervention may be physical activity (PA), with a beneficial effect on both sleep and mental health. Yet, PA levels are declining during adolescent years, with even higher inactivity levels for individuals with psychiatric disorders. Guidance on how to address PA counselling (PAC) among psychiatric adolescents in routine clinical practice has the potential to improve clinical and psychosocial outcomes. Methods During this ongoing randomized waitlist controlled trial, 18 adolescent psychiatric outpatients have been recruited from local clinics and private practices. Those who met inclusion criteria were aged 12 to 18 years, suffered from sleep problems, and had at least one additional mental health diagnosis. Exclusion criteria included organic sleep and brain disorders and changes in medication. At baseline, participants completed questionnaires related to sleep and psychopathology. For the next seven days, participants wore an Actigraph to track PA and sleep patterns. Participants were serially randomized into two groups after baseline: PAC or Treatment as usual (TAU). At 3-month follow-up, all tests were repeated. Additionally, a semi structured interview was conducted with intervention participants. To assess intervention effects, mixed model ANOVAs were conducted for PA, psychopathology, and composite sleep health. The 6-session intervention builds on previous standardized and theory-based PAC programs (Gerber et al., 2019). Results By 2023, follow-up data were available from 12 participants (Mage 15.33 yrs; 75% females). Preliminary data show a significant trend for increased PA on school days, and composite sleep health (p = .07). Yet, compliance of Actigraph wear time was low. No changes were observed for psychopathology. The post-intervention interview revealed positive experiences. Discussion/Conclusion The preliminary data show the feasibility of the intervention. It is likely that improvements in PA and sleep patterns must first stabilize before they can have a meaningful impact on psychopathology. However, more data is needed to confirm the results. The interviews revealed that the content and mode of delivery were generally accepted. Considering the many other obligations adolescents face in their everyday lives, including homework and psychotherapy, the combination of online and face-to-face sessions was well received. Because of the low compliance rate of Actigraph wear time, alternative devices should be considered for this population. References Dahl, R. E., Allen, N. B., Wilbrecht, L., & Suleiman, A. B. (2018). Importance of investing in adolescence from a developmental science perspective. Nature, 554(7693), 441-450. https://doi.org/10.1038/nature25770 Gerber, M., Beck, J., Brand, S., Cody, R., Donath, L., Eckert, A., Faude, O., Fischer, X., Hatzinger, M., Holsboer-Trachsler, E., Imboden, C., Lang, U., Mans, S., Mikoteit, T., Oswald, A., Pühse, U., Rey, S., Schreiner, A. K., Schweinfurth, N., ... Zahner, L. (2019). The impact of lifestyle physical activity counselling in IN-PATients with major depressive disorders on physical activity, cardiorespiratory fitness, depression, and cardiovascular health risk markers: Study protocol for a randomized controlled trial. Trials, 20(1), 1-21. https://doi.org/10.1186/s13063-019-3468-3